Amidu 2009. Matrix Nominal Phrases in Kiswahili Bantu - Tiewa, Kathrin (AAeO - Afrikanistik-Aegyptologie-Online, 2010)
Amidu, Assibi A. 2009. Matrix Nominal Phrases in Kiswahili Bantu. A Study of their Effects on Argument Syntax. [Gram-matical Analyses of African Languages, Volume 34]. Rüdiger Köppe Verlag, Köln. 236 pages; 297 Illustrations; and Index.